Psychosocial Challenges Faced by Albinos in Inclusive Societies and Coping Strategies Practiced by them to address these challenges. A case of Lahore City - Samina Ashraf, Iqra Fatima, (JIE, 2024)
Albinism is a genetic condition characterized by the complete or partial lack of melanin, a pigment responsible for the color of skin, hair, and eyes. Albinism, like all other groups of disabilities, is associated with certain psychosocial challenges in an or inclusive society. The present study aimed at examining the psychosocial challenges faced by persons with albinism in our inclusive society and the coping strategies used by them to address these challenges. For the study, the interpretive phenomenological research design was used.